Metaproteomics reveals methyltransferases implicated in dichloromethane and glycine betaine fermentation by ‘Candidatus Formimonas warabiya’ strain DCMF - Holland, Sophie I.; Vázquez-Campos, Xabier; Ertan, Haluk; Edwards, Richard J.; Manefield, Michael J.; Lee, Matthew (Frontiers in Microbiology, 2022)
Dichloromethane (DCM; CH2Cl2) is a widespread pollutant with anthropogenic and natural sources. Anaerobic DCM-dechlorinating bacteria use the Wood-Ljungdahl pathway, yet dechlorination reaction mechanisms remain unclear and the enzyme(s) responsible for carbon-chlorine bond cleavage have not been definitively identified. Of the three bacterial taxa known to carry out anaerobic dechlorination of DCM, ‘Candidatus Formimonas warabiya’ strain DCMF is the only organism that can also ferment non-chlorinated substrates, including quaternary amines (i.e. choline and glycine betaine) and methanol. Strain DCMF is present within enrichment culture DFE, which was derived from an organochlorine-contaminated aquifer. We utilised the metabolic versatility of strain DCMF to carry out comparative metaproteomics of cultures grown with DCM or glycine betaine. This revealed differential abundance of numerous proteins, including a methyltransferase gene cluster (the mec cassette) that was significantly more abundant during DCM degradation, as well as highly conserved amongst anaerobic DCM-degrading bacteria. This lends strong support to its involvement in DCM dechlorination. A putative glycine betaine methyltransferase was also discovered, adding to the limited knowledge about the fate of this widespread osmolyte in anoxic subsurface environments. Furthermore, the metagenome of enrichment culture DFE was assembled, resulting in five high quality and two low quality draft metagenome-assembled genomes. Metaproteogenomic analysis did not reveal any genes or proteins for utilisation of DCM or glycine betaine in the cohabiting bacteria, supporting the previously held idea that they persist via necromass utilisation.